PKM CATFISH PROCESSED BUSINESS DEVELOPMENT IN SUDAMANIK VILLAGE CIMARGA DISTRICT RANGKASBITUNG - Wiguna, Wahyu; C, Elis C; Nita, Nita; Aryadi, Aryadi; Asrul, Asrul; Daffa, Daffa (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
Food security is one of the determinants of community welfare, especially in the countryside. Efforts to achieve these conditions need cooperation between various elements, one of which is the role of universities through community service activities. Cultivation carried out in Sudamanik Village, Cimarga Subdistrict, Lebak Regency aims to earn income during difficult times in pandemic times. Therefore, this Catfish processed business is a program from students doing community service in Sudamanik Village and can be developed by the Local Community. The method used in this activity through marketing assistance and catfish processing assistance by using kitchen tools that can be used in the manufacture of catfish crackers, namely knives to memfilet / cut catfish and finished cracker dough then to smooth the dough using a mixer and to form the dough into long oblongs by manual use of hand. The results of processing this catfish into catfish crackers are preferred and beneficial for health. Itis expected to help improve the economy of the Sudamanik community in the time of pandemic. Catfish is processed into a ready-to-eat process that is healthy, nutritious, practical and economical. Catfish processing business can be developed in Sudamanik Village as an alternative income if there is a delay in rice harvesting, the high willingness of the community to be able to produce catfish crackers is the beginning of the rise of MSMEs in Sudamanik Village.